2023
DOI: 10.1002/ece3.9812
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally testing mate preference in an avian system with unidirectional bill color introgression

Abstract: Mating behavior can play a key role in speciation by inhibiting or facilitating gene flow between closely related taxa. Hybrid zones facilitate a direct examination of mating behavior and the traits involved in establishing species barriers. The long‐tailed finch (Poephila acuticauda) has two hybridizing subspecies that differ in bill color (red and yellow), and the yellow bill phenotype appears to have introgressed ~350 km eastward following secondary contact. To examine the role of mate choice on bill color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 70 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…It is therefore likely that these genes are involved in mediating the coloration differences between S. beltoni and S. plumbea , the most notable of which is in the beak. These differences in beak color may contribute to promoting prezygotic reproductive isolation, as has been found between subspecies of Long-tailed Finches ( Poephila acuticauda ) [47,48]. Within the genus Sporophila, species have either gray, black, yellow or orange bills [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore likely that these genes are involved in mediating the coloration differences between S. beltoni and S. plumbea , the most notable of which is in the beak. These differences in beak color may contribute to promoting prezygotic reproductive isolation, as has been found between subspecies of Long-tailed Finches ( Poephila acuticauda ) [47,48]. Within the genus Sporophila, species have either gray, black, yellow or orange bills [24].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 15, 2023. ; https://doi.org/10.1101/2023.11.14.567069 doi: bioRxiv preprint color may contribute to promoting prezygotic reproductive isolation, as has been found between subspecies of Long-tailed Finches (Poephila acuticauda) [47,48]. Within the genus Sporophila, species have either gray, black, yellow or orange bills [24].…”
Section: Discussionmentioning
confidence: 99%
“…Bill color phenotyping. Bill color was measured via UV-vis reflectance spectrophotometry for wild-caught and captive-bred adult long-tailed finches following protocols published in prior studies (Griffith and Hooper 2017;McDiarmid et al, 2023). In brief, spectral reflectance of the upper mandible from three consecutive scans per individual were averaged and smoothed using the R package Pavo 2 (Maia et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Spectra were then normalized by their maximum and minimum reflectance values, and the colorimetric variable H3 was calculated for all samples. H3 is a measure of bill hue that represents the wavelength midway between the minimum and maximum reflectance of a surface, which we bounded between 400 and 700 nm (Maia et al, 2019) and has previously been shown to effectively differentiate the bill colors of the two long-tailed finch subspecies and their hybrids (McDiarmid et al, 2023). To supplement reflectance data first examined by Griffith and Hooper (2017) and McDiarmid et al (2023) we measured bill color for an additional 165 wild-caught and 137 captive-bred samples in this study for a total of 948 wild and 550 captive samples with reflectance data (N = 1498 total).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation